S116 GDF-15, the miR-542 cluster and miR-422a are associated with muscle wasting in Intensive Care Unit Acquired Paresis. (12th November 2015) - Paul, RG; Polkey, MI; Kemp, PR; Griffiths, MJD
Abstract : Introduction and aims: Intensive care unit acquired paresis (ICUAP) is a common complication of critical illness, associated with significant morbidity and mortality in patients admitted to the ICU. To date, there has been little success in the identification of patients at risk of acute muscle wasting or potential targets for therapeutic intervention. GDF-15, a TGF-B family member, has been shown to be a potential driver of acute muscle wasting in ICUAP (Crit Care Med 2013;41:982). From previous analyses in ICUAP and other wasting conditions, we hypothesised that pre-surgery expression of microRNAs from the miR-542 family would be higher in patients who would lose significant muscle bulk following surgery, whereas expression of miR-422a would be lower. Methods: A prospective observational study of 40 patients undergoing high-risk cardiothoracic surgery with cardiopulmonary bypass was conducted. Patients underwent pre- and post-operative paired rectus femoris biopsies and blood sampling. Muscle wasting was assessed by ultrasound pre-operatively and at day 7 post surgery. Plasma GDF-15 protein was quantified by ELISA and mRNA and microRNA expression in muscle specimens by RT-PCR. Main results: 52% (21 of 40) patients developed muscle atrophy. Plasma GDF-15 concentration was significantly raised at all sampling time points in patients with significant muscle wasting (wasters) compared to those that did not (non-wasters). miR-542–3p (median 1.9-fold, p = 0.0029), miR-542–5p (median 4.5-fold, p = 0.0346) and miR-424 (median 4.2-fold, p = 0.0040) were higher in pre-operative muscle specimens of wasters compared to non-wasters, whilst miR-422a was lower (median 1.2-fold, p = 0.0176). Expression of these miRNAs significantly correlated with change in rectus femoris cross-sectional area over time (see Figure 1 ). Discussion: Pre-operative expression in muscle of these miRNAs correlates significantly with reductions in muscle bulk after major surgery and cardiopulmonary bypass suggesting that the pre-existing status of the muscle is important in the susceptibility to muscle wasting. Furthermore, as both miR-542–3p/-5p and miR-422a are predicted to regulate p53 activity in opposite directions, these data imply that the p53 stress pathway contributes to this susceptibility. This study identifies these microRNAs as potential therapeutic targets in ICUAP.